DUPLEX COLLECTING SYSTEM WITH ECTOPIC URETEROCOELE A CASE REPORT OF INTRAUTERINE DIAGNOSIS BY ULTRASOUND - HORSAKUL, Pannee (The ASEAN Journal of Radiology, 2023)
A demonstrating case of intrauterine diagnosis of duplex collecting system and ectopic ureterocoele is reported. Early surgical intervention by removal of the dysplastic kidney, its dilated ureter and ectopic ureterocoele can prevent obstruction of the contralateral ureteric orifice and the ipsilateral lower ureter by the ectopic ureterocoele. Comparison and follow up of ultrasound before and after delivery, intravenous pyelogram at 3-month-old, operative and pathological findings are also shown.